Una virtù fuori moda? : La castitas secondo Tommaso d’Aquino - Panero, Marco (La scuola cattolica, 2024)
The study aims to present the Thomistic teaching on the virtue of chastity, to show its charm and strategic character. First of all, the specific object of chastity and its place within the framework of temperance are clarified (§ 1), to then explore the reasons for its necessity, including the connection that chastity has with justice, charity and prudence (§ 2). Like virginity, chastity is not restricted to its material regulation (§ 3), since it refers to a global project of life, in which the purposes of sexual activity find due order (§ 4). The formation of a chaste, affectively mature individual, requires that chastity shape the subject’s own sensitivity, through affective connaturality (§ 5).